An Analysis of the Diverse Structures and Performance of Government Human Resource Development in Indonesia - Marsus, Soffan (Universitas Negeri Semarang, 2024)
Currently, there is a growing demand for heightened professionalism and optimal performance within government institutions, emphasizing efficiency. A discernible trend towards delineating Human Resource Development (HRD) as a distinct entity from Human Resource Management (HRM) is evident in the pursuit of achieving superior standards. This study reexamines the organizational frameworks and performance of government HRD in this evolving landscape, shedding light on the significant contributions made by government HRD to their organizations. This research is crucial for understanding the contribution of government HRD to organizational objectives. Employing qualitative methodologies, the study delves into the organizational structures of HRD entities, identifying three predominant variants: (1) an HRD function existing as a sizable specialized division, (2) a clear separation between HRD and HRM functions, and (3) HRD operating within an HRM Department. Importantly, the scope of roles and functions within HRD is observed to be expanding. Furthermore, HRD institutions are perceived to have transitioned beyond the traditional role of conducting training to actively implementing strategic human resource development initiatives. The Covid-19 pandemic has notably influenced training methodologies, leading to a substantial increase in online training over the pandemic's two-year span. This shift has resulted in breakthroughs and heightened efficiency in the implementation of training initiatives amidst the challenges posed by the pandemic. Given the rarity of studies in this field, it is anticipated that this research will be valuable in ensuring that all government entities achieve effective and efficient operations.